Comparative analysis of Penicillium genomes reveals the absence of a specific genetic basis for biocontrol in Penicillium rubens strain 212 - Requena, Elena; Alonso-Guirado, Lola; Veloso, Javier; Villarino, María; Melgarejo, Paloma; Espeso, Eduardo Antonio; Larena, Inmaculada (Frontiers in Microbiology, 2023)
Penicillium rubens strain 212 (PO212) is a filamentous fungus belonging to the division Ascomycete. PO212 acts as an effective biocontrol agent against several pathogens in a variety of horticultural crops including Fusarium oxysporum f.sp. lycopersici, causing vascular wilt disease in tomato plants. We assembled draft genomes of two P. rubens strains, the biocontrol agent PO212 and the soil isolate S27, which lacks biocontrol activity. We also performed comparative analyses of the genomic sequence of PO212 with that of the other P. rubens and P. chrysogenum strains. This is the first Penicillium strain with biocontrol activity whose genome has been sequenced and compared. PO212 genome size is 2,982 Mb, which is currently organized into 65 scaffolds and a total of 10,164 predicted Open Reading Frames (ORFs). Sequencing confirmed that PO212 belongs to P. rubens clade. The comparative analysis of the PO212 genome with the genomes of other P. rubens and Penicillium chrysogenum strains available in databases showed strong conservation among genomes, but a correlation was not found between these genomic data and the biocontrol phenotype displayed by PO212. Finally, the comparative analysis between PO212 and S27 genomes showed high sequence conservation and a low number of variations mainly located in ORF regions. These differences found in coding regions between PO212 and S27 genomes can explain neither the biocontrol activity of PO212 nor the absence of such activity in S27, opening a possible avenue toward transcriptomic and epigenetic studies that may shed light on this mechanism for fighting plant diseases caused by fungal pathogens. The genome sequences described in this study provide a useful novel resource for future research into the biology, ecology, and evolution of biological control agents.